Diseño de la Red hidrometeorológica como herramienta para el monitoreo y prevención de crecidas e inundaciones, en la subcuenca del rio Puyo para el Gobierno Autónomo Descentralizado Provincial de Pastaza. - Franco Andrade, Mario Lizardo (2024)
The study entitled "Design of the Hydrometeorological Network as a Tool for Flood and Flood Prevention and Monitoring in the Puyo River Sub-basin for the Autonomous Decentralized Provincial Govemment of Pastaza" addressed the need to improve the collection of hydrometeorological data in Pastaza, Ecuador. Its objective is to design a network of stations to optimize the management of water resources and the prevention of natural disasters, considering the work of researchers and the technical criteria of the World Meteorological Organisation. The diagnosis revealed that of the four stations in the subbasin, only one is operational, underlining the urgency of a new network. Using the Thiessen polygon method in ArcGIS 10.8 and a multi- criteria analysis that included altitude, slope, accessibility, and safety, the installation of 20 stations was proposed: 3 hydrological, 4 pluviometric, 9 hydrometric, and 4 meteorological, a tan estimated cost of $607,636.73 over 20 years. An environmental analysis was carried out, which revealed an increase in the anthropogenic area from 53.17% to 68.79% between 1990 and 2018. A social study revealed will improve data coverage and accuracy, strengthen emergency response capacity, and contribute to more efficient management of water resources, complying with legal regulations and ensuring the viability and sustainability of the project.